Ouvidoria no sistema único de saúde: é um espaço de gestão democrática e participativa? - Santos Júnior, Adalberto Fulgêncio dos (2012)
The brazilian society has experienced classical principles of democracy for almost thirty years however citizen involvement remains insufficient when it comes to Public Administration. In doing so, this study aimed to verify whether the Public Health Care System (SUS) Ombudsmen have in fact served as a public management tool giving room to participation and listening to users concerns. The study based itself on the concept that a democratic society is one where civil rights are created as a mean to change and enhance the state (CHAUÍ, 2011). As per Luchman (2007), a participative democracy is an open debate environment of public affairs towards collective interests based on government commitment. Health Care Ombudsman management reports from 2008 to 2011 regarding drug programs have been analyzed allowing for a comparison between the drug lists published by SUS in the same period with the purpose of verifying whether user requests are taken into account. The results showed SUS has helped socialize the state and might very well allow for participation although not yet considered a management instrument once its reports have not been taken into account in the development of drug lists. Based on this study, the SUS General Ombudsman is still in the process of establishing itself as a democratic environment and management instrument.